Mr. Bonaparte of Corsica - Bangs, John Kendrick, 1862-1922 (Salt Lake City, UT : Project Gutenberg, 2002)
"Mr. Bonaparte of Corsica" by John Kendrick Bangs is a historical novel written during the late 19th century. The narrative focuses on the early life of Napoleon Bonaparte, starting with his humble beginnings on the island of Corsica in 1769 and exploring his formative years, personality traits, and the groundwork laid for his future as one of history's most renowned military leaders. The opening of the novel introduces us to the Bonaparte family and the circumstances surrounding the birth of Napoleon, the second of thirteen children. It portrays him as a precocious child, full of confidence and ambition, predicting his future greatness. Through anecdotes from his early years$1 (Bsuch as his fierce determination and leadership over his siblings$1 (BBangs paints a vivid picture of the future emperor's character. The reader is treated to a blend of humor and historical insight, setting the stage for the exploration of Napoleon's journey from a Corsican boy to a military commander on the world stage. (This is an automatically generated summary.)s
Release date is 2002-05-01
This etext was produced from the 1902 Harper and Brothers edition by David Price
Keywords: Napoleon I, Emperor of the French, 1769-1821 -- Humor